Election System for the Chairman of the Neighborhood Units in Sumur Kolong Hamlet: A Study of Political Anthropology - Fernando Holqi, Fikri Gali; Rahman, Rizki Ananda (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2024)
This study aims to analyze the election system of the chairman of the Neighborhood Units in Sumur Kolong Hamlet, Banyuwangi. This is done by identifying 1) the challenge of democracy and the election of the Chairman of the Neighborhood Unit in Sumur Kolong Hamlet and 2) deliberative democracy and feminism in the election of the Chairman of Neighborhood Units. This research uses a qualitative approach with a case study type. Primary data consists of observations and interviews. Meanwhile, secondary data consists of journals and books. The results of the study stated that. The condition causes most people to want to make themselves or their children Priyai until the position is achieved, creating a dynastic political pattern. To limit and eliminate these conditions or phenomena, (W), as the chairman of the community unit, created a concept in the election system for the chairman of the neighborhood unit in Sumur Kolong Hamlet. 1) The Head of the Family carries out the election, 2) the Election is Led by the Chairman of the Incumbent RT, RW, and Religious Leaders, and 3) Candidacy in Open Form; this is an effort to provide constitutional rights of the community.